The influence of leadership on factors related to teachers in Islamic boarding schools - Sary, Fetty Poerwita; Farihin, Ahmad; Tamam, Badrud; Prasetio, Adhi Prasetio; Rahmatika, Aida Fauzia (Edelweiss Applied Science and Technology, 2024)
This study examines the influence of leadership on factors related to teachers in Islamic boarding schools. Being a multicultural country that boasts harmony and peaceful living, Indonesia supports educational policies related to its citizens’ beliefs in the form of Islamic boarding schools. While harboring a sizeable Muslim population, the Islamic boarding school (IBS) with an exceptional curriculum parallel with Islamic teaching, namely pesantren, is developed and led by Kyai, who has a role like principal in regular schools. As the school’s central figure, Kyai’s leadership will inevitably determine the teaching quality of its students. The current study aimed to understand the association between Kyai’s leadership style and teaching team-related factors, mediated by collaboration and a supportive school culture. Questionnaire data was collected from 85 teachers at an Islamic boarding school in the West Java Province of Indonesia. Hypotheses in the tested model were analyzed using the SEM-PLS method. We found that supportive school culture is not associated with distributive leadership. Distributed leadership lacks the mediating role of school culture, while instructional leadership positively impacts job satisfaction and personal confidence. Furthermore, the data suggests that both teacher cooperation and school culture have a negligible influence on the comprehensive framework. Based on those results, in Islamic Boarding Schools, it is important for Kyai to foster a nurturing school environment and promote collaboration among Asatidz (teachers) in their educational roles; these elements have been shown to significantly correlate with the Asatidz’s sense of job fulfillment and their confidence in their teaching abilities.